2018
DOI: 10.1111/liv.13967
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐exome sequencing identifies novel pathogenic variants across the ATP7B gene and some modifiers of Wilson's disease phenotype

Abstract: In a Polish population, genetic screening for WD may help genotype for four variants (p.His1069Gln, p.Gln1351Ter, p.Trp779Ter and c.3402delC), with direct sequencing of all ATP7B amplicons as a second diagnostic step. We also identified some allelic variants that may modify a WD phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 53 publications
(90 reference statements)
2
25
0
Order By: Relevance
“…We suspect that two mutations confirmed as pathogenic, in our case, were present on one allele (uniparental isodisomy), which is rare but has been previously observed [9]. In our recent study of 248 patients with WD, we found three cases with three mutations [10]. As WD is an autosomal recessive disease, pathogenic mutations must be present on two alleles [2].…”
Section: To the Editorssupporting
confidence: 68%
“…We suspect that two mutations confirmed as pathogenic, in our case, were present on one allele (uniparental isodisomy), which is rare but has been previously observed [9]. In our recent study of 248 patients with WD, we found three cases with three mutations [10]. As WD is an autosomal recessive disease, pathogenic mutations must be present on two alleles [2].…”
Section: To the Editorssupporting
confidence: 68%
“…Another reason may be due to the presence of mutations outside the open reading frame of the gene, i.e., in the promoter, introns, the presence of gene rearrangements or possible mutations in other copper-transport chaperone gene. Anna Kluska proved that rare allelic variants in ESD and IN080 increased and decreased the chances for the neurologic phenotype, respectively, while rare variants in APOE and MBD6 decreased the possibilities of WD early manifestation [ 28 ]. It was reported that the AmpliSeq Exome kit usually underestimated the insertions and deletions in exome enrichment products [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anna Kluska proved that rare allelic variants in ESD and IN080 increased and decreased the chances for the neurologic phenotype, respectively, while rare variants in APOE and MBD6 decreased the possibilities of WD early manifestation [ 28 ]. It was reported that the AmpliSeq Exome kit usually underestimated the insertions and deletions in exome enrichment products [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over hundred mutations of ATP7B, including point mutations, deletions and frame-shift, have been reported in patients with WD. Most patients have two different mutations of the gene on each allele encoding the WD gene, called compound heterozygotes [2,3]. This protein product is similar to other ATP-dependent transporters for heavy metals, which is mainly expressed in the liver and mediates copper homeostasis in liver cells.…”
Section: Introductionmentioning
confidence: 99%